Outcomes of Pancreas Retransplantation After Simultaneous Kidney-Pancreas Transplantation Are Comparable to Pancreas After Kidney Transplantation Alone. Issue 3 (March 2015) - Seal, John; Selzner, Markus; Laurence, Jerome; Marquez, Max; Bazerbachi, Fateh; McGilvray, Ian; Schiff, Jeffrey; Norgate, Andrea; Cattral, Mark S.
Abstract : Background: There is a paucity of contemporary data describing the results of pancreas retransplantation (PRT). As a measure of utility, we wished to determine whether PRT could produce equivalent short-term and long-term recipient outcomes to primary pancreas after kidney (PAK) transplantation. Methods: Retrospective analysis of 96 consecutive pancreas only transplants performed from 2003 to May 2012. Primary PAK transplants (n=78) were compared to PRT (n=18). Results: Donor and recipient demographics were similar. Pancreas graft survival was similar for PAK and PRT at 1 year (88.2% vs. 100%) and 3 years (85.1% vs. 85.1%). Pancreas graft failure occurred in 14 PAK and two PRT patients with a mean follow-up of 61.6±38.7 and 37.8±26.1 months, respectively. There were no differences in postoperative length of stay (9.9 days vs. 8.7 days; P =0.9) or postoperative complications in the first 3 months (47.4% vs. 38.9%, P =0.6). At 3-year follow-up, both groups had comparable HBA1c (0.06 vs. 0.05; P =0.8), serum creatinine (116.6 μmol/L v 131.7 μmol/L; P =0.09), and oral glucose tolerance tests. Conclusion: Pancreas retransplantation is a safe and effective therapy for select recipients after graft loss. Pancreas retransplantation is associated with the same risk of postoperative complications and has similar intermediate-term graft survival compared to primary PAK transplantation. Abstract : Pancreas retransplantation is as successful as primary pancreas-after-kidney transplantation with respect to organ function and survival.